2022
DOI: 10.3389/fpsyg.2022.941161
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of leadership and intrinsic motivation: Examining relative importance and moderators

Abstract: This paper provides the first meta-analytic examination of the relationship between leadership and followers' intrinsic motivation. In particular, we examined 6 leadership variables (transformational, ethical, leader-member exchange, servant, empowering, and abusive supervision) using data from 50 independent samples and 21,873 participants. We found that transformational leadership, ethical leadership, leader-member exchange (LMX), servant leadership, and empowering leadership were positively related to intri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…We found that as the year increases, the correlation between humble leadership and task performance increases. Interestingly, Xue et al ( 2022 ) also found the correlation between servant leadership (ethical leadership) and intrinsic motivation increases, as the year increases. However, these findings should be understood carefully, as publication year may relate to a series of factors (e.g., management level and economic condition).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…We found that as the year increases, the correlation between humble leadership and task performance increases. Interestingly, Xue et al ( 2022 ) also found the correlation between servant leadership (ethical leadership) and intrinsic motivation increases, as the year increases. However, these findings should be understood carefully, as publication year may relate to a series of factors (e.g., management level and economic condition).…”
Section: Discussionmentioning
confidence: 98%
“…It is quite interesting to consider the influence of publication year. Because the year may relate to many factors, such as economic conditions and research paradigms (Xue et al, 2022 ). It is also possible that overall study quality increases as the year increases, which may influence the correlations of interest.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Engaging leaders are expected to behave in such a way that they fulfil their followers' work-related basic needs [11] which, in turn, is expected to fuel intrinsic motivation [34]. Schaufeli [11] proposes four components of EL, namely, empowering, strengthening, inspiring, and connecting.…”
Section: Intrinsic Motivation In the Jd-r Leadership Modelmentioning
confidence: 99%